Penerimaan Komunitas Montase terhadap Representasi Ras Asia di Amerika dalam Film Minari - Ega Riadiska; Sumekar Tanjung (Fakultas Ilmu Komunikasi UKWMS, 2023)
Films are able to provide entertainment as well as influence the attitudes and views of the audience. Audience has an important position in receiving messages. This study aims to explain the Montage community's reception of the representation of Asian race in America on the Minari film. The dynamics of adaptation, crisis, and family are closely related to the identity of Asian immigrants trying to reach their hopes in the destination country. The researcher applied Stuart Hall's reception analysis by conducting a thorough observation of Minari's film to determine the encoding and conducting interviews with three informants from the Montase community to conduct the decoding analysis. The results of this study describe two classifications of informant positions, namely dominant position and negotiated position. Differences in background, culture, and knowledge affect the informants' meaning of the representation of the Asian race in Minari.ABSTRAK Film mampu memberikan hiburan sekaligus mempengaruhi sikap dan pandangan audiens. Sebagai penonton, audiens memiliki posisi penting dalam penerimaan pesan. Penelitian ini bertujuan untuk menjelaskan resepsi komunitas Montase terhadap representasi ras Asia di Amerika dalam film Minari. Dinamika adaptasi, krisis, dan keluarga lekat dengan identitas imigran Asia yang berupaya menggapai harapan di negara tujuan. Peneliti mengaplikasikan pendekatan resepsi milik Stuart Hall dengan melakukan pengamatan menyeluruh terhadap film Minari untuk menentukan encoding dan melakukan wawancara terhadap tiga orang informan dari komunitas Montase untuk melakukan analisis decoding. Hasil penelitian ini menguraikan dua klasifikasi posisi informan yakni dominant position dan negotiate position. Perbedaan latar belakang, budaya, dan pengetahuan mempengaruhi pemaknaan informan terhadap representasi ras Asia dalam Minari.